Small RNA fingerprinting of Alzheimer's disease frontal cortex extracellular vesicles and their comparison with peripheral extracellular vesicles - Cheng, Lesley; Vella, Laura J.; Barnham, Kevin J.; McLean, Catriona; Masters, Colin L.; Hill, Andrew F. (Journal of extracellular vesicles, 2020)
Alzheimer's disease is a progressive neurodegenerative disorder, with the strongest disease-associated changes observed at clinical or end-stage disease. Transcriptomic deregulation of miRNA expression can spread via "horizontal" RNA transfer through extracellular vesicles (EVs) to act in conjunction with proteins, leading to changes in mRNA, which can provide early signals to indicate forthcoming neuropathological changes in the brain. Here, we analysed the small RNA content, in particular, miRNA, contained in brain-derived EVs isolated from the frontal cortex of Alzheimer's subjects (n = 8) and neurological control subjects (n = 9). Brain-derived EVs were found to contain an upregulation of disease-associated miRNA. RNA species from brain-derived EVs were correlated with miRNA profiles obtained from matching total brain homogenate. These results provide a blueprint into the biological pathways potentially effected during disease that may be assisted by brain-derived EV RNA horizontal transfer.We also correlated the miRNA changes in the brain with those detected in peripheral EVs collected from serum of Alzheimer's disease patients (n = 23, and healthy controls, n = 23) and revealed a panel of miRNA that could be used as a liquid brain biopsy. Overall, our study provides the first interrogation of the small RNA contents in brain-derived EVs and how they could be used to understand the early pathological changes in Alzheimer's disease which will benefit the development of an early diagnostic blood test.